Linear IgA bullous dermatosis: report of an exuberant case - Beatriz Cavalcanti de Souza; Nádire Cristina Freire Pontes Fregonesi; Antônio José Tebcherani; Ana Paula Galli Sanchez; Valéria Aoki; Juliana Christien Fernandes (Sociedade Brasileira de Dermatologia, 2013)
Linear immunoglobulin A dermatosis is a rare autoimmune bullous disease, but the most common autoimmune bullous dermatosis in children. We report a typical exuberant case of linear IgA dermatosis in a ten-month old child, who showed good response to treatment with corticosteroids and dapsone.